Risk communication when serving customers with food allergies in restaurants in the United States - Wen, Han (Kansas State University, 2015)
Food allergies affect nearly 15 million Americans, and accommodating customers with food allergies has become a challenge for the restaurant industry. One third of the fatal food allergy reactions occurred in restaurants, and it is important for the restaurant industry to properly communicate and manage the food allergy risks. This study explored perceived risks and risk communication related behaviors of restaurant staff when serving customers with food allergies by using both qualitative (interviews) and quantitative (online survey) approaches. Telephone interviews with 16 restaurant managers were audio-recorded, transcribed verbatim, and organized to identify themes. Most participants were aware of the severity of food allergy reactions but perceived that it was the customers’ responsibilities communicating their food allergies with restaurant staff before placing their orders. Training for service staff on food allergies and risk communication topics were limited, and some managers perceived such training unnecessary for restaurant business. Findings from interviews were used to develop an online survey instrument. The survey instrument was pilot-tested and distributed to restaurant employee panels by an online survey research firm. Of 1,328 accessed the survey, 316 usable survey responses (23.8%) were collected from full-service restaurant service staff. Data analyses included descriptive statistics, independent samples t-test, ANOVA, and regression analyses. Results indicated that limited information about food allergies was provided on printed (35.1%) or online menus (28.2%), and very few restaurants had separate menus (8.5%) or complete ingredient lists (14.6%) for customers with food allergies. Meanwhile, restaurant servers lacked knowledge about common food allergens (12.7% correct), differences between food allergies and intolerances (34.2% correct), and government regulations related to food allergies (15.5% correct). Most restaurant servers (82.0%) agreed or strongly agreed that initiating communication and preventing food allergy reactions were responsibilities of customers with food allergies. Perceived severity of food allergy reactions, previous communication training, sources of media exposure, and perceived responsibilities of preventing food allergy reactions were found to influence restaurant servers’ risk reduction and communication behaviors (R²=0.367, p<0.001). Restaurateurs, foodservice educators, food allergy advocates, and policy makers may use these findings when developing food allergy training and strategies to prevent food allergy reactions in restaurants.
Keywords: Food allergy; Restaurant; Manager; Servers; Risk perception; Risk communication; Communication (0459); Health Education (0680); Management (0454)